Supply Need Analysis of Strategic Commodities in Supply Chain Management Development in Surabaya - Ignatia Martha Hendrati; Nuruni Ika Kusuma Wardhani; Hery Pudjo Prastyono; Sishadiyati (Journal of Economics, Business, and Government Challenges, 2019)
The problem of food sufficiency is a basic human need so that the availability of food for the people of Surabaya City must always be guaranteed. Law Number 7 of 1996 concerning Food, mandates that the government and the community are responsible for realizing Food Security. The Government organizes the regulation, guidance, control and supervision of sufficient food availability, both in quantity and quality and safety and nutritious, evenly distributed and affordable by the purchasing power of the people. The rate of increase in food demand is faster than the rate of increase in production capacity. Surabaya as a city of trade and services does not have sufficient agricultural land so that the supply of strategic commodities highly depends on supplies from outside the region which cause vulnerability to supply availability and price instability. Based on the description above, intensive monitoring of food price volatility in several markets and food wholesalers in the city of Surabaya is needed in order to maintain supply stability and price stability. One alternative to overcome the problems as above is with the development of the Supply Chain Management logistics city. In the long run according to the results that will be obtained in this study, it is expected to increase the role of PD. Pasar Surya in maintaining supply availability and price stability.